The internal properties of the bioadhesive bond - Marshall, Paul (2000)
The movement and concentration of water inside hydrophilic matrices and the bioadhesive bonds formed by them have been proposed as important factors in the bioadhesion of hydrophilic matrices (Smart et al, 1991, and Mortazavi and Smart, 1993). This thesis has developed a non-invasive magnetic resonance imaging (MRI) technique to spatially resolve the self-diffusion coefficient (SDC) and concentration profiles of water inside the bioadhesive bonds formed by dry and hydrated hydrophilic matrices. The bioadhesive interaction between mucin and adhesive may affect the network structure and diffusion retarding properties of either polymer. The mobility of solutes may be used as an indicator of such changes. This thesis has developed a fluorescence recovery after photobleaching (FRAP) technique to measure the mobility of fluorescently tagged dextrans in the mucin and adhesive polymer networks.